Nietzsche and Jewish culture - Golomb, Jacob (New York : Routledge, 1997)
This unique collection of essays explores the reciprocal relationship between Nietzsche and Jewish culture. It is organized in two parts: the first examines Nietzsche's attitudes towards Jews and Judaism: the second Nietzsche's influence on Jewish intellectuals as diverse and as famous as Franz Kafka, Martin Buber, Franz Rosenzweig and Sigmund Freud. Each carefully selected essay explores one aspect of Nietzsche's relation to Judaism and German intellectual history, from Heinrich Heine to Nazism.
pt. I. Nietzsche's relations to Jews, Judaism and Jewish culture. Nietzsche, Anti-Semitism and the Holocaust / Steven E. Aschheim ; A Post-Holocaust Re-examination of Nietzsche and the Jews: vis-a-vis Christendom and Nazism / Weaver Santaniello ; "Mongols, Semites and the Pure-Bred Greeks": Nietzsche's Handling of the Racial Doctrines of His Time / Hubert Cancik ; Heine, Nietzsche and the Idea of the Jew / Sander L. Gilman ; Nietzsche on Judaism and Europe / Josef Simon ; Nietzsche and the Jews: The Structure of an Ambivalence / Yirmiyahu Yovel -- pt. II. Nietzsche's Jewish reception. Nietzsche, Kafka and Literary Paternity / Stanley Corngold ; Nietzsche and the Marginal Jews / Jacob Golomb ; Freud in his Relation to Nietzsche / Peter Heller ; Mahler and the Vienna Nietzsche Society / William J. McGrath ; Zarathustra's Apostle: Martin Buber and the Jewish Renaissance / Paul Mendes-Flohr ; Diasporas / Gary Shapiro.
Includes bibliographical references (pages 263-266) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Views on Judaism; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Influence; Nietzsche, Friedrich Wilhelm, -- 1844-1900; Jews -- Germany -- Intellectual life; Germany -- Intellectual life -- 20th century; Juifs -- Allemagne -- Vie intellectuelle; Allemagne -- Vie intellectuelle -- 20e siècle.; PHILOSOPHY -- History & Surveys -- Modern; Influence (Literary, artistic, etc.); Intellectual life; Jews -- Intellectual life; Judaism; Germany; 1900-1999